Dyspepsia: incidence of a non-ulcer disease in a controlled trial of ranitidine in general practice. Issue 6521 (8th March 1986) - Saunders, J H; Oliver, R J; Higson, D L
Abstract : Patients who presented to their family doctors with previously uninvestigated dyspepsia of at least two weeks' duration were recruited into a placebo controlled trial of treatment with ranitidine (150 mg twice daily) for six weeks. All patients were examined by endoscopy before treatment, and for those with macroscopical abnormalities the examination was repeated after treatment. Of the 604 patients recruited, 559 had endoscopy, of whom 171 (30%) had no apparent abnormality. Of the 388 patients remaining, one third had two or more lesions. The high incidence of underlying disease was coupled with low accuracy in unaided clinical diagnosis. After endoscopy 496 patients with persistent symptoms (median duration six to eight weeks) were randomly allocated to treatment and then reviewed every two weeks. Complete remission of symptoms occurred in 76% of patients who were taking ranitidine and in 55% who were taking placebo (p less than 0.000004). Of those with non-ulcer dyspepsia, significantly more became symptom free taking ranitidine compared with placebo (p less than 0.002). Ranitidine healed most duodenal ulcers (80%) and gastric ulcers (90%) within four weeks. Tolerance to ranitidine was good, and the incidence of complaints was similar on placebo.